Peningkatan Hasil Belajar Siswa Menggunakan Media Kartu Positif Negatif pada Mata Pelajaran Matematika Pokok Bahasan Penjumlahan Bilangan Bulat Kelas IV di SDN 04 Mamben Lauk Tahun Pelajaran 2016/2017 - Ittihad Ittihad (FONDATIA, 2017)
Research has been conducted on the Improvement of Student Learning Outcomes Using Positive Card Cards On Mathematics Subjects Summation of Sum Total Class IV Students at SDN 04 Mamben Lauk Lesson Year 2016/2017. The purpose of this research is to know how to IncreaseStudent Learning Result Using Positive Negative Positive Media on Mathematics Subject Matter of Sum Sumed of Student of Class IV in SDN 04 Mamben Lauk Lesson Year 2016/2017. The types of research used are classroom action research and data analysis techniques used in this research are reduction, data presentation, verification, and development of instruments used to summarize data, encode, straighten the theme and make clusters about the data about improving learning outcomes Fourth grade students of SDN 04 Mamben Lauk. Based on the results of the study found a significant result that is the increase in student learning outcomes after using the positive negative card media many of the students whose learning outcomes to be better than before, the original average value is 6.3 after conducting research the average value to be 8.2. There is an increase in student learning outcomes in mathematics subjects of the sum of integers after the application of this positive negative card media.